A29 Kynurenine 3-monooxygenase interacts with huntingtin at the outer mitochondrial membrane. (September 2018) - Breda, Carlo; Swaih, Aisha M; Repici, Mariaelena; Giorgini, Flaviano
Abstract : Background: Kynurenine 3-monooxygenase (KMO), an outer mitochondrial membrane protein, catalyses the conversion of l-kynurenine to the neurotoxin 3-hydroxykynurenine (3-HK) – thereby playing a critical role in the kynurenine pathway (KP). Increased KMO activity likely contributes to the toxicity observed in neurodegenerative disorders by enhancing levels of 3-HK and the excitotoxin quinolinic acid (QUIN). Notably, genetic and pharmacological inhibition of KMO ameliorates disease-relevant phenotypes in models of Huntington's disease (HD). Aims: This study interrogates the subcellular localisation of human KMO and explores its interaction with the huntingtin (HTT) protein. Methods: Confocal analysis was employed to explore KMO localisation and bimolecular fluorescence complementation (BiFC) and transmission electron microscopy was used to investigate KMO and HTT interactions in HEK293T cells. Results: We found that KMO exclusively localises to mitochondria when expressed in HEK293T cells. A deletion of a C-terminal portion of KMO (tKMO) which contains a putative transmembrane domain causes the mislocalisation of the enzyme from mitochondria to other cellular compartments, suggesting a critical function for this region in mitochondrial targeting. We also found an interaction between KMO and both WT and mutant HTT fragments at the outer mitochondrial membrane. Notably, the strength of this interaction was inversely correlated to the length of the HTT polyglutamine expansion. No interaction between tKMO and HTT was observed indicating that mitochondrial localization of KMO is likely critical for HTT/KMO interactions. Conclusions: This study suggests that KMO and HTT may interact at the outer mitochondria membrane. The biological significance of this interaction will be explored in future experiments.